2019
DOI: 10.1002/joc.6057
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of wet‐season rainfall over Iran by the Madden–Julian Oscillation, Indian Ocean Dipole and El Niño–Southern Oscillation

Abstract: The intra-seasonal variation of precipitation over Iran is examined in terms of the combined effects of the Madden-Julian Oscillation (MJO), Indian Ocean Dipole (IOD) and El Niño-Southern Oscillation (ENSO), using daily observations during the wet season (October-May) from 1961 to 2015. We have examined how the probability of daily rainfall above the upper tercile varies across MJO phases during positive and negative IOD and ENSO states. The results indicate that the response of Iran's wet-season rainfall to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
(48 reference statements)
0
12
1
Order By: Relevance
“…The results of the ENSO influence are somewhat consistent with the report of Karabörk and Kahya (2009) about the significant ENSO contribution to Turkey's precipitation and rivers streamflows, but contradict with other regional studies (e.g., Cullen et al 2002;Pourasghar et al 2019). Cullen et al (2002) pointed to the strong influence of the NAO to six regional rivers discharge, but we have obtained only weak SRCs between the precipitations and NAO, as well with the NDVIs.…”
Section: ) Possible Predictors Of Ndvicontrasting
confidence: 61%
See 1 more Smart Citation
“…The results of the ENSO influence are somewhat consistent with the report of Karabörk and Kahya (2009) about the significant ENSO contribution to Turkey's precipitation and rivers streamflows, but contradict with other regional studies (e.g., Cullen et al 2002;Pourasghar et al 2019). Cullen et al (2002) pointed to the strong influence of the NAO to six regional rivers discharge, but we have obtained only weak SRCs between the precipitations and NAO, as well with the NDVIs.…”
Section: ) Possible Predictors Of Ndvicontrasting
confidence: 61%
“…Cullen et al (2002) pointed to the strong influence of the NAO to six regional rivers discharge, but we have obtained only weak SRCs between the precipitations and NAO, as well with the NDVIs. More recently, Pourasghar et al (2019) indicated that rainfalls in Iran (October-May) are more affected by the IOD than by ENSO. Indeed, we have obtained, respectively, a moderate SRC of 0.7 and 0.55 between March and April NDVI and December month of IOD index, named the dipole mode index (DMI), but these values are almost the same as between NDVIs and ENSO links.…”
Section: ) Possible Predictors Of Ndvimentioning
confidence: 99%
“…Some investigators have listed the prevailing years of the positive or negative IOD phase (Meyers et al ., 2007; Lestari et al ., 2018; Pourasghar et al ., 2019). We used these provided lists and particularly the list obtained by the Australian Bureau of Meteorology (http://www.bom.gov.au/climate/iod/) to re‐generate Figure 3a,b for those days of the SWPP or SWWD that concur with the IOD negative phase (Figure S1a,b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The above‐mentioned discussion shows some discrepancies with the findings of Pourasghar et al . (2019). They reported that “the negative (positive) IOD strengthens (suppresses) the MJO‐rainfall relationship in the wet and dry MJO phases.” However, our study shows that, for the Nov–Apr period, the prevalence of MJO phase 1 suppresses the evolution of the IOD negative phase and subsequently, diminishes the effect of this negative phase on precipitation variability over southwestern parts of Iran.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation